(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Objective: To determine whether glass ceiling beliefs mediate the relationship between workplace spirituality and subjective success among women managers serving in Banks in India. Method: Data was collected from 500 women managers serving in 3 public sector, 3 Indian private sector and 4 foreign banks in India. Structural Equation Modelling was run to determine the relationship among the constructs. Result: It was found that Workplace Spirituality significantly predicted Subjective Success. Additionally, two glass ceiling beliefs viz., denial and resilience mediated the relationship between workplace spirituality and subjective success. Conclusion: Organisations must employ workplace spirituality interventions to im-prove the subjective success of women. Originality: The findings offer a novel perspective on improving women’s chances of career advancement by enhancing workplace spirituality. This is the first in-depth study to focus on the mediating effect of glass ceiling beliefs and study the percep-tion of women regarding the glass ceiling in Banks in India.